Ten stages of American Indian genocide - Cameron, Susan Chavez; Phan, Loan T. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
To better serve the American Indian population, it is essential for educators, including professionals in the helping fields, to understand how the United States federal government over the past 200 years used six different strategies to address “America’s Indian problem.” Using the Stanton’s Ten Stages of Genocide (2013), the authors explore American Indian holocaust and genocide and their impact on the behavioral health and well-being of Native people in Indian Country. The purpose of this manuscript is to expand and deepen the views of educators in such a way that influences and effects their professional practice with the American Indian populations they serve. Para servir al pueblo Indio Americano mejor, es esencial que los educadores, incluyendo a los profesionales en los campos de servicio, entiendan que por los últimos doscientos años el gobierno federal de los Estados Unidos ha usado seis estrategias diferentes dirigiéndose al "problema Americano de los Indios." Los autores usan Las Diez Etapas de Genocidio de Staton, o Staton's Ten Stages of Genocide (2013), para explorar el holocausto y el genocidio de Indio-Americanos y el impacto que ambos han tenido en la salud del comportamiento y el bienestar del pueblo Nativo en su tierra. El propósito del manuscrito es el expandir y profundizar el punto de vista de los educadores de modo que incluya y afecte su práctica profesional con la población Indio Americana que sirven.